Diesel Exhaust Induces Mitochondrial Dysfunction, Hyperlipidemia, and Liver Steatosis. Issue 9 (September 2019) - Yin, Fen; Gupta, Rajat; Vergnes, Laurent; Driscoll, Will S.; Ricks, Jerry; Ramanathan, Gajalakshmi; Stewart, James A.; Shih, Diana M.; Faull, Kym F.; Beaven, Simon W.; Lusis, Aldons J.; Reue, Karen; et al.
Abstract : Objective: Air pollution is associated with increased cardiovascular morbidity and mortality, as well as dyslipidemia and metabolic syndrome. Our goal was to dissect the mechanisms involved. Approach and Results: We assessed the effects of exposure to air pollution on lipid metabolism in mice through assessment of plasma lipids and lipoproteins, oxidized fatty acids 9-HODE (9-hydroxyoctadecadienoic) and 13-HODE (13-hydroxyoctadecadienoic), lipid, and carbohydrate metabolism. Findings were corroborated, and mechanisms were further assessed in HepG2 hepatocytes in culture. ApoE knockout mice exposed to inhaled diesel exhaust (DE, 6 h/d, 5 days/wk for 16 weeks) exhibited elevated plasma cholesterol and triglyceride levels, increased hepatic triglyceride content, and higher hepatic levels of 9-HODE and 13-HODE, as compared to control mice exposed to filtered air. A direct effect of DE exposure on hepatocytes was demonstrated by treatment of HepG2 cells with a methanol extract of DE particles followed by loading with oleic acid. As observed in vivo, this led to increased triglyceride content and significant downregulation of ACAD9 mRNA expression. Treatment of HepG2 cells with DE particles and oleic acid did not alter de novo lipogenesis but inhibited total, mitochondrial, and ATP-linked oxygen consumption rate, indicative of mitochondrial dysfunction. Treatment of isolated mitochondria, prepared from mouse liver, with DE particles and oleic acid also inhibited mitochondrial complex activity and β-oxidation. Conclusions: DE exposure leads to dyslipidemia and liver steatosis in ApoE knockout mice, likely due to mitochondrial dysfunction and decreased lipid catabolism. Abstract : Supplemental Digital Content is available in the text.